Ochrobactrum anthropi: An unusual emerging pathogen - Aishwarya Babu; Sunita M Bhatawadekar; Mahadevan Kumar; Meera S Modak (Wolters Kluwer Medknow Publications, 2023)
Ochrobactrum anthropi is an organism which is commonly distributed in the environment and water sources including normal saline, antiseptic solutions, and dialysis fluid. However, it is an opportunistic pathogen, especially in critically ill or immunocompromised patients. The presence of central venous catheter line is a risk factor. Here, we report two cases of bacteremia caused by O. anthropi in patients undergoing chemotherapy.